Evaluation on the Temperature and Calcination Time During Sol-gel Coating of TiO2 on Iron Foam substrate - Raden Dadan Ramdan; Luqman Haris; Hendra Hermawan; Bambang Sunendar (Mesin, 2017)
Iron foam is iron based material which is widely applied due to its unique properties. However since corrosion is also a problem for this material, coating with innert material is required in enhancing its applications. In the present research, TiO2 coating is performed on iron foam suface by sol-gel dipping method. Focus is given on the study of the effect of calcinations temperature and time on the coating characteristics. TiCl4 is used as the precursor with concentration of 0.3 M, added with 1M HCl solution and chitosan soluation with concentration of 1%. Calcination is performed at temperature of 400, 500 dan 600oC and calcinations time of 1 and 3 hours inside controlled gas furnace using nitrogen atmosphere. Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) characterization data shows that TiO2 particles form on the iron foam substrate. SEM characterization on the sample heated at 400oC and heating time of 1 hour shows the formation of nano particle titania (0.06 Î¼m) which is homogeneously distributed with less agglomeration than others and considered as the best sample in the present research. As the temperature and time of calcinations increase, more inhomogeneous particle distribution and bigger particles form.